2017
DOI: 10.1016/j.jjcc.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to medication and characteristics of Japanese patients with non-valvular atrial fibrillation

Abstract: Our study showed that the prevalence of non-adherence to medications was 14% in NVAF patients. Frequent daily dosing was an independent risk factor for non-adherence to medication (UMIN-CTR No. UMIN 000023514).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
3
14
1
2
Order By: Relevance
“…Although MPR is an indirect estimate of "true" adherence, our results suggest that overall adherence for warfarin is optimal in the Japanese population, showing a higher rate of adherence than reports from other countries. 19,20) The reason for high adherence in the Japanese population is uncertain, but our results are comparable with those of another recent report from Japan. 21) Suzuki et al analyzed self-reported questionnaires among 378 Japanese patients with non-valvular AF (77% warfarin users) and found that 86% of patients were adherent to anticoagulation therapy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although MPR is an indirect estimate of "true" adherence, our results suggest that overall adherence for warfarin is optimal in the Japanese population, showing a higher rate of adherence than reports from other countries. 19,20) The reason for high adherence in the Japanese population is uncertain, but our results are comparable with those of another recent report from Japan. 21) Suzuki et al analyzed self-reported questionnaires among 378 Japanese patients with non-valvular AF (77% warfarin users) and found that 86% of patients were adherent to anticoagulation therapy.…”
Section: Discussionsupporting
confidence: 87%
“…19,20) The reason for high adherence in the Japanese population is uncertain, but our results are comparable with those of another recent report from Japan. 21) Suzuki et al analyzed self-reported questionnaires among 378 Japanese patients with non-valvular AF (77% warfarin users) and found that 86% of patients were adherent to anticoagulation therapy. They hypothesized that the high adherence rate was owing to patient characteristics of long-standing history of AF and comorbid heart failure; however, it is unclear whether this may hold true for the cohort in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Treatment persistence with rivaroxaban will also be revealed in the XAPASS. Treatment persistence is a major concern in stroke prevention because discontinuation of anticoagulation therapy affects the stroke risk in patients with AF . Persistence with rivaroxaban in the XANTUS was 80% at 1 year .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment persistence is a major concern in stroke prevention because discontinuation of anticoagulation therapy affects the stroke risk in patients with AF. 16 Persistence with rivaroxaban in the XANTUS was 80% at 1 year. 11 This is higher than in recent US studies 17,18 under the supervision of a steering committee.…”
Section: Age and Body Weightmentioning
confidence: 99%
“…Dosing frequency with once-daily dosing relative to more frequent (two to four times) daily dosing regimens facilitates adherence for chronic cardiovascular drugs, as well as antihypertensive drugs. Once-daily dosing of ASM monotherapy would likely improve adherence [18][19][20].…”
Section: Plos Onementioning
confidence: 99%